The effect of a diabetes prevention program on dietary quality in women with previous gestational diabetes - Sharleen O'Reilly; Vincent Versace; Mohammadreza Mohebbi; Siew Lim; Edward Janus; James Dunbar (BMC, 2019)
Abstract Background Women with gestational diabetes have low diet quality. We evaluated the effectiveness of a group-based lifestyle modification program for improvement of dietary quality in women with previous gestational diabetes predominantly within their first postnatal year. Methods Women were randomised to intervention (n = 284) or usual care (n = 289). Dietary data was collected at baseline and twelve months using a food frequency questionnaire and recoded into the Australian Recommended Food Score (ARFS). Mixed model analyses investigated the intervention effect on ARFS (per-protocol-set (PPS) excluded women without the minimum intervention exposure). Results Baseline mean total ARFS was low (31.8 ± 8.9, maximum score = 74) and no significant changes were seen in total ARFS (Cohen's D = − 0.06). 2% reduction in alcohol for intervention (0.05, 0.26) compared with − 1% for usual care (Odds ratio: 0.68; 95%CI 0.46, 0.99). Dairy ARFS sub-category significantly improved (low fat/saturated fat foods) in the intervention group over time compared with usual care for the PPS analysis (dairy + 0.28 in intervention (95%CI 0.08, 0.48) compared with + 0.02 in usual care (95%CI -0.14, 0.18) (group-by-treatment interaction p = 0.05, Cohen's D = 0.14)). Conclusions Engaging with the intervention improved aspects of diet quality that aligned with minimum intervention exposure, but the total diet quality remains low. Further research is needed to improve diabetes prevention program engagement. Trial registration Australian New Zealand Clinical Trials Registry ANZCTRN12610000338066, April 2010.